1999
DOI: 10.1242/dev.126.4.781
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of transmembrane and released forms of neuregulin during spinal cord and neuromuscular synapse development

Abstract: We mapped the distribution of neuregulin and its transmembrane precursor in developing, embryonic chick and mouse spinal cord. Neuregulin mRNA and protein were expressed in motor and sensory neurons shortly after their birth and levels steadily increased during development. Expression of the neuregulin precursor was highest in motor and sensory neuron cell bodies and axons, while soluble, released neuregulin accumulated along early motor and sensory axons, radial glia, spinal axonal tracts and neuroepithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Similarly, pharmacological and surgical-induced death of axons contributes to apoptotic Schwann cell death, and exogenous NRG1 administration can rescue death, induced by loss of axons (Ciutat et al, 1996;Winseck et al, 2002). Embryonic DRG axons and motor neurons express NRG1, which accumulates along axonal tracts (Falls et al, 1993;Loeb et al, 1999;Marchionni et al, 1993;Orr-Urtreger et al, 1993, Taveggia et al, 2005 and would therefore be available at the right time to regulate precursor survival. As mentioned before, SCP numbers are severely reduced in mice, in which NRG1 signaling has been disrupted by genetic inactivation of either the NRG1 gene or its receptors ErbB2 or ErbB3 (Garratt et al, 2000b;Meyer and Birchmeier, 1995;Morris et al, 1999;Riethmacher et al, 1997;Woldeyesus et al, 1999).…”
Section: Axonal-glial Interactions In Developing Nerves and Their Imp...mentioning
confidence: 99%
“…Similarly, pharmacological and surgical-induced death of axons contributes to apoptotic Schwann cell death, and exogenous NRG1 administration can rescue death, induced by loss of axons (Ciutat et al, 1996;Winseck et al, 2002). Embryonic DRG axons and motor neurons express NRG1, which accumulates along axonal tracts (Falls et al, 1993;Loeb et al, 1999;Marchionni et al, 1993;Orr-Urtreger et al, 1993, Taveggia et al, 2005 and would therefore be available at the right time to regulate precursor survival. As mentioned before, SCP numbers are severely reduced in mice, in which NRG1 signaling has been disrupted by genetic inactivation of either the NRG1 gene or its receptors ErbB2 or ErbB3 (Garratt et al, 2000b;Meyer and Birchmeier, 1995;Morris et al, 1999;Riethmacher et al, 1997;Woldeyesus et al, 1999).…”
Section: Axonal-glial Interactions In Developing Nerves and Their Imp...mentioning
confidence: 99%
“…RB neurons) promote myelination of both dorsal and ventral axons that project from distantly located neurons in the hindbrain and spinal cord. Because the Ig-like domain of Nrg1 II binds extracellular matrix at synapses in other contexts, limiting diffusion and potentially increasing the signaling potency (Li and Loeb, 2001; Loeb et al, 1999; Pankonin et al, 2005), it seems likely that Nrg1 type II acts to promote myelination via a short-range mechanism. For example, RB, CoPA, and RS neurons all participate in the spinal cord escape response circuit, and it is possible that RB neurons express Nrg1 type II signals to regulate the myelination status of their synaptic partners.…”
Section: Discussionmentioning
confidence: 99%
“…However, these and other studies (Brinkmann et al, 2008) report normal myelination in the spinal cord in Nrg1 and ErbB mutants, despite evidence from pioneering in vitro and ex vivo studies (Bermingham-McDonogh et al, 1997; Marchionni et al, 1993) that established Nrg1 signals as regulators of development, migration, or proliferation of oligodendrocytes, the myelinating cells of the CNS. The roles of other Nrg1 isoforms in CNS myelination are not well-known, although different Nrg1 isoforms regulate synapse formation, heart development, and other processes (Liu et al, 2010; Loeb et al, 1999; Nave and Salzer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, spliced forms of Neuregulin 1 (NRG1) yield neurotrophic factors that play essential roles in promoting MN survival, supporting axonal, and neuromuscular development and maintenance (29)(30)(31)(32)(33)(34)(35). NRG1 is expressed by spinal MNs, with particular localization at the subsurface cisterns close to postsynaptic sites of cholinergic C synapses (36,37).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we showed that treatment with an AAV coding for the full-length form of NRG1-III improves motor function of hindlimb muscles and increases MN survival in SOD1 G93A mice (40). Importantly, NRG1-I expressed by the Schwann cells has a crucial role in axonal regeneration and remyelination (41), in development of NMJs (31) and in muscle reinnervation (42). Thus, overexpression of NRG1-I causes neuromuscular functional improvement, maintaining muscle innervation, and also increasing MN survival in SOD1 G93A mice (43).…”
Section: Introductionmentioning
confidence: 99%